The relations of state bodies with public institutions are based on sustainable and diverse forms of communication, affecting the susceptibility and transparency of the implemented decisions and programmes, the level of trust and the public opinion on the - Aryn, Е.М.; Aryn, Р.С. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The relations of state bodies with public institutions are based on sustainable and diverse forms of communication, affecting the susceptibility and transparency of the implemented decisions and programmes, the level of trust and the public opinion on the part of the population to the state policy. The article reveals the fundamental changes in the foundations of the state system, the implementing institutions, the positioning of Kazakhstan in the group of countries of high development, the use of efficient and flexible communication links with the society. The objective process of growth of social and economic activity of the population, the multilateral participation in the discussion of decisions taken by state bodies, respectively causes the significant changes in the form and combination of communications. In this regard, the experience of the development of state communications in modern Kazakhstan is no exception. For the short period, from the historical point of view, the time period in Kazakhstan forms its own model for managing communications between the authorities and the society. This model is currently provided with both legislative and normative regulations, as well as organizational and personnel, information and technological potential. Based on these statements, all these processes organically fit into the policy of competitive, transparent and pragmatic development of the country, the policy of deepening democratic principles of the government. The active use of new communications of the authorities creates the inherent ‘environment or space’ of positive and constructive ideas and solutions in the society. The statement is justified that the design of a modern model of communication links by the state demonstrates the growing role of social networks, which are currently the basis for the mass character and efficiency of the information space. Internet resources, e-government, networking giants as Twitter, Instagram, Facebook, and the leaders’ portals by public opinion have significantly ‘redefined’ the road map of the communications of the authorities